Salicaceae Endophytes Modulate Stomatal Behavior and Increase Water Use Efficiency in Rice - Rho, Hyungmin; Van Epps, Victor; Wegley, Nicholas; Doty, Sharon L.; Kim, Soo-Hyung (Frontiers in Plant Science, 2018)
Previous studies demonstrated that bacterial and yeast endophytes isolated from the Salicaceae family promote growth and alleviate plant stress. To determine the physiological pathways through which endophytes affect host plant water relations, we investigated plant water potential, water use, and stomatal responses of rice plants to endophyte inoculation under CO2 enrichment and water deficit conditions. We found decreases in stomatal conductance during the daytime and decreases in stomatal density of rice by endophytes. In addition, we observed increases in ABA concentrations in rice leaves with endophytes, which supports the impacts of endophytes on the stomatal responses. Due to the stomatal responses, accumulated total transpiration over time was significantly decreased by endophytes while biomass was either maintained or slightly increased. These led to increases in water use efficiency of the plants at harvest. Three different endophyte strains produced the same results in host plant water relations and stomatal responses. These stomatal responses were also observed under elevated CO2 conditions, and the increase in water use efficiency was greater under water deficit conditions. This increase in water use efficiency was positively correlated to daily light integral during the experiments. Our results provide physiological mechanisms of endophytes increasing water use efficiency. We suggest that the main reason was stomatal closure and alteration of stomatal density while photosynthesis might not be affected.